Evaluation of arboreal and shrub strata in a silvopastoral system in Colombian high Andean tropics - Escobar-Pachajoa, Laura Dayana (2019)
Introduction. Silvopastoral systems are presented as an alternative for the sustainable use of natural resources, so there is a need to identify potential species for their establishment in the high tropics. Objective. The objective was to evaluate the initial growth of eight woody species in a silvopastoral design for water source protection. Materials and methods. The study was carried out in the Obonuco research center of Corporacion Colombiana de Investigacion Agropecuaria (Pasto, Colombia) between September 2017 and June 2018. A randomized block design was developed in a factorial arrangement, where tree/bush species differentiated by their growth habit interacted (high stratum: Cedrela montana, Quercus humboldtii, Ficus andicola; middle stratum: Salix babylonica, Alnus acuminata, Smallanthus pyramidalis; lower stratum: Morella pubescens and Sambucus nigra) and altitude (2750, 2770 and 2800 masl) with four repetitions to evaluate morphometric variables and seedling quality. Results. In the variable height the best behavior was presented in Ficus andicola at 2750 masl with 191.37 cm and Alnus acuminata at 2800 masl with 181.83 cm. In stem diameter Ficus andicola stood out at 2750 masl with 42.98 mm, Smallanthus pyramidalis at 2800 masl with 37.24 mm, and Sambucus nigra at 2800 masl with 8.16 mm. The number of regrowths did not show a significant effect of the interaction, and as seedlings, Quercus humboldtii at 2750 and 2700 masl and Ficus andicola at 2750 masl showed the best quality of individuals; while Cedrela montana showed mortality at the three altitudes evaluated. Conclusions. Native species stood out for their adaptibility, reflected in fast and optimal growth and development, which evidences its great potential to be evaluated in silvopastoral systems in an associated way to decide its multiple benefits and potential contribution to the sustainable development of the livestock in the region.